Perbedaan Kadar TNF-α pada Penderita Tuberkulosis Paru Sebelum dan Sesudah Satu Bulan Terapi Obat Anti Tuberkulosis - Kuncara, Rachmad Bayu; Purlinda, Devi Etivia; Setyaji, Yoki; Sulistyasmi, Wiwit (Jaringan Laboratorium Medis, 2025)
Pulmonary tuberculosis is an infectious disease caused by Mycobacterium tuberculosis. Patients diagnosed with pulmonary tuberculosis undergo Anti-Tuberculosis Drug (OAT) therapy for six months. In the first two months, known as the intensive phase, patients receive a combination of OATs such as isoniazid, rifampicin, ethambutol, and pyrazinamide. TNF-α is a pro-inflammatory cytokine that plays a crucial role in granuloma formation to contain the spread of Mycobacterium tuberculosis. This study aims to determine the difference in TNF-α levels in pulmonary tuberculosis patients before and after one month of OAT therapy. The study used an observational analytic design with a prospective cohort approach without comparison. A total of 17 newly diagnosed pulmonary tuberculosis patients at Bangetayu, Kedungmundu, and Tlogosari Wetan Health Centers, Semarang City, were included. TNF-α levels in serum samples were measured using the ELISA method. The mean TNF-α level before OAT therapy was 110.09±100,48 pg/mL, while after one month of therapy, it decreased to 90,05±60,12 pg/mL. The statistical analysis using the Mann-Whitney test yielded a p-value of 0.228 (p 0.05), indicating that there was no statistically significant difference in TNF-α levels before and after one month of anti-tuberculosis drug (OAT) therapy. However, the mean TNF-α levels showed a decreasing trend, which, although not statistically significant, may suggest an initial immunological response to the treatment. The researcher recommends further studies with a larger sample size and longer observation period—such as until the end of the intensive phase or the completion of therapy—in order to obtain more representative and statistically significant results regarding TNF-α dynamics during tuberculosis treatment.